2017
DOI: 10.1021/acs.langmuir.6b04558
|View full text |Cite
|
Sign up to set email alerts
|

Facet-Specific Adsorption of Tripeptides at Aqueous Au Interfaces: Open Questions in Reconciling Experiment and Simulation

Abstract: The adsorption of three homo-tri-peptides, HHH, YYY and SSS, at the aqueous Au interface is investigated, using molecular dynamics simulations.We find that consideration of surface facet effects, relevant to experimental conditions, opens up new questions regarding interpretations of current experimental findings. Our well-tempered metadynamics simulations predict the rank ordering of the tri-peptide binding affinities at aqueous Au (111) In a separate set of simulations, we predict the structures of the adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 84 publications
3
33
0
Order By: Relevance
“…Since there have been no MD studies of the peptides on a mercury surface, we can only compare our results to studies with the adsorption of peptides on other metallic surfaces. A similar interfacial behavior was found for an His‐rich octapeptide on a Au(111) surface as well as for other peptides and proteins . An enhanced adsorption of the protein tagged with His residues compared to its wild‐type form was also observed .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there have been no MD studies of the peptides on a mercury surface, we can only compare our results to studies with the adsorption of peptides on other metallic surfaces. A similar interfacial behavior was found for an His‐rich octapeptide on a Au(111) surface as well as for other peptides and proteins . An enhanced adsorption of the protein tagged with His residues compared to its wild‐type form was also observed .…”
Section: Resultsmentioning
confidence: 99%
“…This illustrates that even a relatively high positive voltage cannot fully repel the positively charged residues from the surface. Metadynamics studies on the adsorption of the amino acids and tripeptides on a Au(111) surface revealed [36] that adsorption free energies of both histidine forms are very similar, 13 kJ.mol À 1 (for protonated histidine) and 11 kJ.mol À 1 (for non-protonated histidine), thus explaining the similarities in the adsorption behavior of the HIE and HIP states of the H-wire.…”
Section: H-wire Conformation In Watermentioning
confidence: 99%
“…[6][7][8][9][10][11] While experimental efforts to resolve the molecular-level structure of the biotic/abiotic interface are evolving, at present molecular dynamics (MD) simulations can provide a key complementary approach to elucidate the structure and interactions of biomolecules adsorbed at aqueous metal interfaces. 5,7,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] However, the quality of information that can be obtained from molecular simulation is dependent on the model, including the force-field (FF); i.e., how adequately we can capture and describe the interactions between all components of the interface.…”
Section: Introductionmentioning
confidence: 99%
“…23,31,32 For example, there is a strong body of evidence (primarily drawn from molecular simulation sources) that water is more strongly ordered at the (100) surface of noble metals than at the (111) surface, which is reported to confer differences in the adsorption modes of (bio)molecules at the (111) and (100) metal interfaces. [16][17][18][19]23,27,33 Density functional theory (DFT) calculations have predicted that, in vacuo, a single molecule of water adsorbs more strongly at the interface of Pd, and Pt, than to Au and Ag. [34][35][36][37][38] This might lead to a more strongly bound, and ordered, first layer of liquid water molecules at the Pd(111) interface compared with the Au/Ag(111) interface, 33,[39][40][41] which is likely to affect how (bio)molecules adsorb to these different aqueous metal interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For example, thermal hysteresis proteins, a group of serum proteins commonly present in organisms living in cold environments, bind to specific faces of ice crystals to enable their antifreeze activity 13,14 . Recent theoretical studies point to the possibility of facet-dependent selective binding of amino acids, peptides, proteins, and DNA to crystal surfaces containing metals [15][16][17][18][19] . Here, we experimentally prove the concept that facet engineering may be utilized to tune the nanocrystal-biomolecule association for refining biological applications of crystalline nanomaterials.…”
mentioning
confidence: 99%